Doping of polycyclic aromatic chromophores into melamine-formaldehyde networks: An organic room-temperature phosphorescence platform with high stability and excellent processability - Xichang Ou; Shijun Lu; Zhaowei Lan; Qianyi He; Shaolin Lu; Shaoheng Yang; Laixing Pang; Jing Li; Dengchong Feng; Qi Guo; Yuzhao Yang; Zhongke Yuan; et al. (Chemical Engineering Journal, 2026)

Anaerobic digestion of recalcitrant organics and emerging contaminants in pharmaceutical wastewater for carbon neutrality and bioresource recovery: A critical review - Xinru Niu; Tao Zhang; Yao Xu; Jiaxin Ou; Chengzhen Meng; Fan Li; Lan Tang; Yong Hu; Chao Rong; Dapeng Li; Zhe Kong (Bioresource Technology, 2026)

Mechanical behavior and critical state constitutive model of granite soil-rock mixture subjected to drying-wetting cycles - Youneng Liu; Hongming Li; Hongri Zhang; Dongyi Ya; Ou Guo; Tianzhu Lan; Jianqing Jiang (Bulletin of Engineering Geology and the Environment, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Electric-field-induced ultrafast and selective ZIF-8 filling in graphene membrane pores for precision dye desalination - Jialu Li; Zhonghao Xu; Yangdong He; Sheng Shi; Sihan Ye; Liyun Zhang; Lan Ma; Jian Zhen Ou; Hao Yu (Desalination, 2026)

Enrichment effects of vegetation patches on soil water content depend on precipitation and vegetation conditions: A global meta-analysis - Hui-Hua Xu; Zhi-Yun Jiang; Jing-Yi Ding; Xue Guo; Yi-Jia Wang; Xiao-Yan Li; Jia-Lan Feng; Yu-Yao Ou (Journal of Hydrology, 2025)

Hyperoside extends lifespan in Caenorhabditis elegans through SEK-1/PMK-1/SKN-1 pathway - Xin-Tian Yu; Lin Shi; Qiong Huang; Bao Li; Yan-Qing Li; Li-Lan Ou; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2025)

Efficient Adsorption of Dye Pollutant by Anchoring Zr-MOF@GO Composite Matrix Microspheres: Performance and Mechanism Insights - Qianhui Ou; Yan Xiong; Li Chen; Deyong He; Chuxiang Zhou; Lan Wang (Water, Air, & Soil Pollution, 2025)

Exploration of the development of a food safety risk index system for chemical contamination of aquatic products - Qiqi Liu; Yijun Ou; Mhungu Florence; Yan Li; Yanyan Wang; Yuhua Zhang; Lan Liu; Jiangbo Lei; Lili Huang; Sixuan Wu; Rongfei Peng; Zhijun Bai; et al. (Food Control, 2025)

In vivo fiber-optic fluorescent sensor for real-time pH monitoring of tumor microenvironment - Zesen Li; Ni Lan; Zhongyuan Cheng; Fangzhou Jin; Enlai Song; Zhiyuan Xu; Yongkang Zhang; You-Zhen Feng; Xiangran Cai; Yang Ran; Bai-Ou Guan (Chemical Engineering Journal, 2024)

Mechanisms and clinical landscape of N6-methyladenosine (m6A) RNA modification in gastrointestinal tract cancers - Dan-Hua Zhu; Kun-Kai Su; Xiao-Xi Ou-Yang; Yan-Hong Zhang; Xiao-Peng Yu; Zu-Hong Li; Seyedeh-Sara Ahmadi-Nishaboori; Lan-Juan Li (Molecular and Cellular Biochemistry, 2024)
Epigenetics encompasses reversible and heritable chemical modifications of non-nuclear DNA sequences, including DNA and RNA methylation, histone modifications, non-coding RNA modifications, and chromatin rearrangements. In addition to well-studied DNA and histone methylation, RNA methylation has emerged as a hot topic in biological sciences over the past decade. N6-methyladenosine (m6A) is the most common and abundant modification in eukaryotic mRNA, affecting all RNA stages, including transcription, translation, and degradation. Advances in high-throughput sequencing technologies made it feasible to identify the chemical basis and biological functions of m6A RNA. Dysregulation of m6A levels and associated modifying proteins can both inhibit and promote cancer, highlighting the importance of the tumor microenvironment in diverse biological processes. Gastrointestinal tract cancers, including gastric, colorectal, and pancreatic cancers, are among the most common and deadly malignancies in humans. Growing evidence suggests a close association between m6A levels and the progression of gastrointestinal tumors. Global m6A modification levels are substantially modified in gastrointestinal tumor tissues and cell lines compared to healthy tissues and cells, possibly influencing various biological behaviors such as tumor cell proliferation, invasion, metastasis, and drug resistance. Exploring the diagnostic and therapeutic potential of m6A-related proteins is critical from a clinical standpoint. Developing more specific and effective m6A modulators offers new options for treating these tumors and deeper insights into gastrointestinal tract cancers.

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

Emergence and mobilization of a novel lincosamide resistance gene lnu(I): From environmental reservoirs to pathogenic bacteria - Zhishuang Yang; Tianjing Lan; Hongyan Luo; Pei Li; Mingshu Wang; Renyong Jia; Shun Chen; Mafeng Liu; Xinxin Zhao; Qiao Yang; Ying Wu; Shaqiu Zhang; et al. (Science of The Total Environment, 2024)

Socioeconomic status, lifestyle and risk of incident dementia: a prospective cohort study of 276730 participants - Ya-Nan Ou; Yan-Bo Zhang; Yu-Zhu Li; Shu-Yi Huang; Wei Zhang; Yue-Ting Deng; Bang-Sheng Wu; Lan Tan; Qiang Dong; An Pan; Ren-Jie Chen; Jian-Feng Feng; et al. (GeroScience, 2023)

Characteristics of atmospheric carbonyls pollution in winter around petrochemical enterprises over North China - Jin-he Wang; Ou-yang Li; Xue Yang; Guang Pan; Guo-lan Fan; Hou-yong Zhang; Zhi-yong Xia; Xiao-yan Sun; Hong-yu Xu; Yan-jun Chen; Chao Zhu (Air Quality, Atmosphere & Health, 2023)

Adverse impacts of development on the deltamethrin-exposed host Ephestia elutella (Lepidoptera: Pyralidae) on population parameters of Habrobracon hebetor (Hymenoptera: Braconidae) - Xiu-Qin Wang; Hou-Ding Ou; Hao-Xi Li; Lan Wei; Yao Huang; Mao-Fa Yang (Crop Protection, 2023)

Enhanced virulence of genetically engineered Autographa californica nucleopolyhedrovirus owing to accelerated viral DNA replication aided by inserted ascovirus genes - Huan Yu; Chang-Jin Yang; Yi-Yi Ou-Yang; Yue Tong; Hui-Yu Lan; Jia-Min Gan; Shi-Wei Li; Ding-Yi Bai; Guo-Hua Huang (Pesticide Biochemistry and Physiology, 2023)

Sex-specific markers developed by 2b-RAD and genome sequencing reveal an XX/XY sex-determination system in mud carp (Cirrhinus molitorella) - Haiyang Liu; Weiwei Xia; Bingjie Li; Lan Liu; Yakun Wang; Qing Luo; Mi Ou; Xinping Zhu; Kunci Chen; Jian Zhao (Aquaculture, 2023)

Transcriptome analysis and co‐expression network reveal the mechanism linking mitochondrial function to immune regulation in red crucian carp ( Carassius auratus red var) after Aeromonas hydrophila challenge - Ning‐Xia Xiong; Xu‐Ying Kuang; Zi‐Xuan Fang; Jie Ou; Shi‐Yun Li; Jia‐Hui Zhao; Jin‐Fang Huang; Ke‐Xin Li; Rou Wang; Lan‐Fen Fan; Sheng‐Wei Luo; Shao‐Jun Liu (Journal of Fish Diseases, 2022)
Aeromonas hydrophila is a common pathogen of freshwater fish. In this study, A. hydrophila infection was shown to cause tissue damage, trigger physiological changes as well as alter the expression profiles of immune‐ and metabolic‐related genes in immune tissues of red crucian carp (RCC). Transcriptome analysis revealed that acute A. hydrophila infection exerted a profound effect on mitochondrial oxidative phosphorylation linking metabolic regulation to immune response. In addition, we further identified cellular senescence, apoptosis, necrosis and mitogen‐activated protein kinase signal pathways as crucial signal pathways in the kidney of RCC subjected to A. hydrophila infection. These findings may have important implications for understanding modulation of immunometabolic response to bacterial infection.

Treadmill Exercise Relieves Chronic Restraint Stress-induced Cognitive Impairments in Mice Via Activating Protein Phosphatase 2A - Wenjing Zhang; Haining Ou; Borui Zhang; Meifeng Zheng; Lan Yan; Yang Chen; Kwok-Fai So; Li Zhang (Neuroscience Bulletin, 2021)

Detection and quantification of Aeromonas schubertii in Channa maculata by TaqMan MGB probe fluorescence real‐time quantitative PCR - Chun Liu; Yanming M. Guo; Jizhen Z. Cao; De‐Feng Zhang; Ou‐Qin Chang; Kaibin Li; Fang Wang; Cun‐Bin Shi; Lan Jiang; Qing Wang; Li Lin (Journal of Fish Diseases, 2019)
Aeromonas schubertii is a major epidemiological agent that threatens cultured snakeheads ( Channidae ) and has caused great economic losses in fish‐farming industries in China in recent years. In present study, a specific TaqMan minor groove binder ( MGB ) probe fluorescence real‐time quantitative PCR ( qPCR ) assay was developed to rapidly detect and quantify A. schubertii . A pair of qPCR primers and a TaqMan MGB probe were selected from the rpoD gene, which were shown to be specific for A. schubertii . A high correlation coefficient ( R 2 = 0.9998) in a standard curve with a 103% efficiency was obtained. Moreover, the qPCR method's detection limit was as low as 18 copies/μl, which was 100 times more sensitive than that of conventional PCR . The detection results for the A. schubertii in pond water and fish tissue were consistent with those of the viable counts. Bacterial load changes detected by qPCR in different tissues of snakeheads infected with A. schubertii showed that the gills and intestines may be the entry for A. schubertii , and the spleen and kidney are major sites for A. schubertii replication. The established method in present study should be a useful tool for the early surveillance and quantitation of A. schubertii .

Sodium P-Aminosalicylic Acid Improved Manganese-Induced Learning and Memory Dysfunction via Restoring the Ultrastructural Alterations and γ-Aminobutyric Acid Metabolism Imbalance in the Basal Ganglia - Chao-Yan Ou; Yi-Ni Luo; Sheng-Nan He; Xiang-Fa Deng; Hai-Lan Luo; Zong-Xiang Yuan; Hao-Yang Meng; Yu-Huan Mo; Shao-Jun Li; Yue-Ming Jiang (Biological Trace Element Research, 2017)

Effects of norfloxacin on hepatic genes expression of P450 isoforms (CYP1A and CYP3A), GST and P-glycoprotein (P-gp) in Swordtail fish (Xiphophorus Helleri) - Ximei Liang; Lan Wang; Ruikang Ou; Xiangping Nie; YuFeng Yang; Fang Wang; Kaibin Li (Ecotoxicology, 2015)

Association of hypertension and obesity with renal cell carcinoma risk: a report from the Shanghai Men’s and Women’s Health Studies - Tian Shen; Xiao-Ou Shu; Yong-Bing Xiang; Hong-Lan Li; Hui Cai; Yu-Tang Gao; Wei Zheng; Loren Lipworth (Cancer Causes & Control, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Fruit and vegetable intake and the risk of colorectal cancer: results from the Shanghai Men’s Health Study - Emily Vogtmann; Yong-Bing Xiang; Hong-Lan Li; Emily B. Levitan; Gong Yang; John W. Waterbor; Jing Gao; Hui Cai; Li Xie; Qi-Jun Wu; Bin Zhang; Yu-Tang Gao; et al. (Cancer Causes & Control, 2013)

Transcriptional responses of maize seedling root to phosphorus starvation - Hai-Jian Lin; Jian Gao; Zhi-Ming Zhang; Ya-Ou Shen; Hai Lan; Li Liu; Kui Xiang; Maojun Zhao; Shufeng Zhou; Yong-Zhong Zhang; Shi-Bin Gao; Guang-Tang Pan (Molecular Biology Reports, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Cationic liposome coupled endostatin gene for treatment of peritoneal colon cancer - Keng-Li Lan; Fu Ou-Yang; Sang-Hue Yen; How-Ling Shih; Keng-Hsin Lan (Clinical & Experimental Metastasis, 2010)

Family cancer history affecting risk of colorectal cancer in a prospective cohort of Chinese women - Gwen Murphy; Xiao-Ou Shu; Yu-Tang Gao; Bu-Tian Ji; Michael Blaise Cook; Gong Yang; Hong Lan Li; Nathaniel Rothman; Wei Zheng; Wong-Ho Chow (Cancer Causes & Control, 2009)

Family history of malignancies and risk of breast cancer: prospective data from the Shanghai women’s health study - Briseis A. Kilfoy; Yawei Zhang; Xiao-Ou Shu; Yu-Tang Gao; Bu-Tian Ji; Gong Yang; Hong Lan Li; Nathaniel Rothman; Wong-Ho Chow; Wei Zheng (Cancer Causes & Control, 2008)